Hydrological Discharge and Hydropower Capacity Assessment for Sustainable Watershed Management - Saputri, Utamy Sukmayu; Niar Armayanti; Thomasonan Lutfie Prananto (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2026)
The fluctuation of Cicatih River discharge presents a significant challenge in maintaining the operational performance of the Ubrug Hydropower Plant (HPP) in Sukabumi. Dependence on seasonal variations directly influences turbine efficiency and the continuity of electricity generation. This study aims to analyze the existing discharge of the Cicatih River, determine the efficiency of Ubrug HPP turbines, and evaluate the optimal discharge based on seasonal conditions. A quantitative approach was applied using the F.J. Mock hydrological simulation method to estimate discharge from rainfall data, potential evapotranspiration (PET), and watershed characteristics. Turbine efficiency was assessed through comparison of theoretical and actual power output during 2015–2024. Findings indicate that annual discharge varied from 12.13 m³/s to 17.65 m³/s, with turbine efficiency ranging between 83% and 86%, averaging 85.1%. The optimal discharge for maximum generation (≥15 m³/s) occurred mainly during the rainy season, whereas in the dry season discharge averaged about 12 m³/s, falling below the optimal threshold and reducing electricity output. Overall, the Ubrug HPP demonstrates stable and relatively high turbine efficiency, but maximum capacity is limited by seasonal discharge availability. Hence, integrated water management strategies are required to secure sustainable power supply and enhance operational efficiency of the plant.